PENGARUH METODE SENSORI DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN - NASIR, NASIR (Universitas Islam Negeri Raden Intan Lampung, 2014)
The purpose of this research is to study the influence of multisensory method to increase children prior ability in reading skill. It was done by using quasi experiment with pre-test post-test control group design. The result has shown that there was a significant infuence of using multisensory method to increase children’ prior ability in reading skill. Therefore, it is better for teacher of early education to teach reading by giving reading stimuation which pays attention to the children development factors and arranges in comfortable ways.